5 worlds. Book 5, The emerald gate - Siegel, Mark, 1967-; Siegel, Alexis; Bouma, Xanthe; Rockefeller, Matt; Sun, Boya (New York : Random House, 2021)
In the conclusion to the '5 Worlds' series, the final battle looms as Oona, Jax, and An Tzu travel to the treacherous world of Grimbo (E)! There, Oona must light the last beacon to save the 5 Worlds, but first she has to find it! When Jax saves an old friend, Oona is given a clue to the green beacon's location.
Map on endpapers.
3.2.
3-6.
Keywords: Heroes -- Comic books, strips, etc -- Juvenile fiction; Interplanetary voyages -- Comic books, strips, etc -- Juvenile fiction; Adventure stories; Science fiction comic books, strips, etc; Heroes -- Fiction; Interplanetary voyages -- Fiction; Adventure and adventurers -- Fiction; Science fiction; Cartoons and comics; Action and adventure comics; Science fiction comics; Graphic novels; Comics (Graphic works).; Heroes -- Juvenile fiction; Interplanetary voyages -- Juvenile fiction